ANALISIS PENGENDALIAN INTERNAL PERSEDIAAN BARANG DAGANG PADA BISNIS RITEL STUDI KASUS TOKO BASMALAH - Saodah Zahrol Maulida; Shalehoddin Shalehoddin (Politeknik Negeri Ambon, 2026)
Introduction: This study began with the importance of internal control management of merchandise inventory in the retail business, which is an important asset and has a direct impact on the company's operational continuity and financial performance. The Basmalah store in the Jungcangcang branch was chosen as the object of this study because it is a partnership retailer with a large turnover and a wide variety of inventory, requiring an effective control system to minimize the risk of stockouts, damage to goods, loss of goods, and fraud.Methods: The method used in this study was a qualitative approach with a case study method, which included interviews, observations, and documentation of the processes of receiving, storing, recording, and monitoring inventory. Results: The results of the study indicate that the implementation of internal controls on merchandise inventory at Basmalah Store has functioned well and is in accordance with internal control regulations. This includes segregation of duties, restrictions on access to storage, and periodic inventory checks both physically and using the system. In practice, minor operational weaknesses were also identified, such as human error in stock recording during peak hours and occasional delays in system updates. However, this study also found several shortcomings, such as limited storage space, which forces some goods to be stored outside, thereby allowing for damage to the quality of goods and dependence on certain suppliers, which can cause disruptions in supply and increased costs.Conclusion and suggestion: This study focused on one branch of the store and applied qualitative methods, so the results cannot be applied to the entire Basmalah chain or other retailers. To overcome this problem, this study suggests strengthening goods receiving procedures, changing warehouse layout, and diversifying suppliers in order to improve the efficiency of internal control of merchandise inventory in similar retail businesses. Therefore, it is recommended that Basmalah Store management prioritize warehouse expansion and supplier diversification as immediate corrective actions to safeguard inventory assets and sustain business operations. Keywords: Internal control, Merchandise inventory, Retail business